Pneumonia, Meningitis, and Septicemia in Adults and Older Children in Rural Gambia: 8 Years of Population-Based Surveillance. (29th July 2022) - Green, Edward W; Ndiaye, Malick; Hossain, Ilias M; Olatunji, Yekini A; Sahito, Shah M; Salaudeen, Rasheed; Badji, Henry; Manjang, Ahmed; Ceesay, Lamin; Hill, Philip C; Greenwood, Brian; Mackenzie, Grant A
Abstract: Background: Representative data describing serious infections in children aged ≥5 years and adults in Africa are limited. Methods: We conducted population-based surveillance for pneumonia, meningitis, and septicemia in a demographic surveillance area in The Gambia between 12 May 2008 and 31 December 2015. We used standardized criteria to identify, diagnose, and investigate patients aged ≥5 years using conventional microbiology and radiology. Results: We enrolled 1638 of 1657 eligible patients and investigated 1618. Suspected pneumonia, septicemia, or meningitis was diagnosed in 1392, 135, and 111 patients, respectively. Bacterial pathogens from sterile sites were isolated from 105 (7.5%) patients with suspected pneumonia, 11 (8.1%) with suspected septicemia, and 28 (25.2%) with suspected meningitis. Streptococcus pneumoniae (n = 84), Neisseria meningitidis (n = 16), and Staphylococcus aureus (n = 15) were the most common pathogens. Twenty-eight (1.7%) patients died in hospital and 40 (4.1%) died during the 4 months after discharge. Thirty postdischarge deaths occurred in patients aged ≥10 years with suspected pneumonia. The minimum annual incidence was 133 cases per 100 000 person-years for suspected pneumonia, 13 for meningitis, 11 for septicemia, 14 for culture-positive disease, and 46 for radiological pneumonia. At least 2.7% of all deaths in the surveillance area were due to suspected pneumonia, meningitis, or septicemia. Conclusions: Pneumonia, meningitis, and septicemia in children aged ≥5 years and adults in The Gambia are responsible for significant morbidity and mortality. Many deaths occur after hospital discharge and most cases are culture negative. Improvements in prevention, diagnosis, inpatient, and follow-up management are urgently needed. Abstract : Disease incidence and outcome calculations need prospective population-based data and postdischarge follow-up. We use 8 years of surveillance to highlight the etiology, incidence, outcome, and high burden of pneumonia, sepsis, and meningitis in older children and adults. in rural Gambia.